In Vitro and In Vivo Preclinical Testing of Pericyte‐Engineered Grafts for the Correction of Congenital Heart Defects. Issue 4 (18th February 2020) - Alvino, Valeria Vincenza; Kilcooley, Michael; Thomas, Anita C.; Carrabba, Michele; Fagnano, Marco; Cathery, William; Avolio, Elisa; Iacobazzi, Dominga; Ghorbel, Mohamed; Caputo, Massimo; Madeddu, Paolo
Abstract : Background: We have previously reported the possibility of using pericytes from leftovers of palliative surgery of congenital heart disease to engineer clinically certified prosthetic grafts. Methods and Results: Here, we assessed the feasibility of using prosthetic conduits engineered with neonatal swine pericytes to reconstruct the pulmonary artery of 9‐week‐old piglets. Human and swine cardiac pericytes were similar regarding anatomical localization in the heart and antigenic profile following isolation and culture expansion. Like human pericytes, the swine surrogates form clones after single‐cell sorting, secrete angiogenic factors, and extracellular matrix proteins and support endothelial cell migration and network formation in vitro. Swine pericytes seeded or unseeded (control) CorMatrix conduits were cultured under static conditions for 5 days, then they were shaped into conduits and incubated in a flow bioreactor for 1 or 2 weeks. Immunohistological studies showed the viability and integration of pericytes in the outer layer of the conduit. Mechanical tests documented a reduction in stiffness and an increase in strain at maximum load in seeded conduits in comparison with unseeded conduits. Control and pericyte‐engineered conduits were then used to replace the left pulmonary artery of piglets. After 4 months, anatomical and functional integration of the grafts was confirmed using Doppler echography, cardiac magnetic resonance imaging, and histology. Conclusions: These findings demonstrate the feasibility of using neonatal cardiac pericytes for reconstruction of small‐size branch pulmonary arteries in a large animal model.